2021
DOI: 10.4103/sjg.sjg_249_21
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease, affecting almost one-third of the general population and 75% of obese patients with type 2 diabetes. The aim of this article is to review the current evidence concerning the role of quercetin, a natural compound and flavonoid, and its possible therapeutic effects on this modern-day disease. Despite the fact that the exact pathophysiological mechanisms through which quercetin has a hepatoprotective effect on NAFLD are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…These above results were consistent with the results reported in the literature that rutin and quercetin exhibited hepatoprotective effects [29][30][31][32][33][34][35][36][37]. Liu et al [29] tried to investigate the molecular mechanisms underlying rutin's hypolipidemic and hepatoprotective effects in NAFLD.…”
Section: Histopathological Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…These above results were consistent with the results reported in the literature that rutin and quercetin exhibited hepatoprotective effects [29][30][31][32][33][34][35][36][37]. Liu et al [29] tried to investigate the molecular mechanisms underlying rutin's hypolipidemic and hepatoprotective effects in NAFLD.…”
Section: Histopathological Studiessupporting
confidence: 88%
“…The data showed that quercetin appears to be a promising hepatoprotective compound. Sotiropoulou et al [33] clearly demonstrated that quercetin had potent antioxidative stress action and inhibitory effects on hepatocyte apoptosis, inflammation, and generation of reactive oxygen species, factors which were linked to the development of the disease. Ying et al [34] also showed that oral administration of quercetin at doses of 30-60 mg/kg to hyperlipidemic rats for 14 days was highly effective in decreasing the levels of serum TC, TG, LDL-C, ALT and AST.…”
Section: Histopathological Studiesmentioning
confidence: 99%
“…Except that capsaicin and cucurbitacin B have high toxicity in mice, the other compounds do not produce obvious toxicity or adverse effects in acute/chronic animal toxicity test or cytotoxicity test, representing their potentials as safe and effective therapeutics drugs or nutritional supplements for the treatment of liver diseases. In fact, some of these compounds, including betaine, caffeine, chlorogenic acid, curcumin, EGCG, genistein, hesperidin, lipoic acid, naringenin, quercetin, resveratrol, sulforaphane, vitamin C and vitamin E, have been reported to be effective and safe in preventing or alleviating the symptoms of liver diseases patient in randomized controlled trials [9,[11][12][13][14]30,45,86,103,145,157,200,226,316].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is a natural flavonoid compound (Fig. 3f) and is readily available from various fruits and vegetables, such as berries, apples, onions, broccoli, pepper and tomato [200]. In the CCl 4 -induced rat liver fibrosis model, quercetin normalizes the liver function and fibrosis markers through balancing profibrogenic/antifibrogenic factors, promoting HSCs apoptosis, or inhibiting Bcl-2/Bax-mediated hepatocytes apoptosis, oxidative state, and NFкB/IкBα-p38 MAPK-mediated inflammation [201,202].…”
Section: Natural Compounds Derived From Edible Plantsmentioning
confidence: 99%
“…It possesses several pharmacological properties, including antioxidant activity against free radicals, antibacterial properties, and cancer-fighting properties. Acacia rice is a rich source of quercetin and contains a high amount of this compound [39]. Quercetin is a flavonoid with potent oxidative properties and many studies have shown that it can significantly reduce lipid accumulation and SREBP1c and XBP-1 expression in adipocytes.…”
Section: Quercetinmentioning
confidence: 99%